Oxytocin in the anterior cingulate cortex attenuates neuropathic pain and emotional anxiety by inhibiting presynaptic long-term potentiation - Li, Xu-Hui; Matsuura, Takanori; Xue, Man; Chen, Qi-Yu; Liu, Ren-Hao; Lu, Jing-Shan; Shi, Wantong; Fan, Kexin; Zhou, Zhaoxiang; Miao, Zhuang; Yang, Jiale; Wei, Sara; et al. (Cell reports (Cambridge), 2021)
Oxytocin is a well-known neurohypophysial hormone that plays an important role in behavioral anxiety and nociception. Two major forms of long-term potentiation, presynaptic LTP (pre-LTP) and postsynaptic LTP (post-LTP), have been characterized in the anterior cingulate cortex (ACC). Both pre-LTP and post-LTP contribute to chronic-pain-related anxiety and behavioral sensitization. The roles of oxytocin in the ACC have not been studied. Here, we find that microinjections of oxytocin into the ACC attenuate nociceptive responses and anxiety-like behavioral responses in animals with neuropathic pain. Application of oxytocin selectively blocks the maintenance of pre-LTP but not post-LTP. In addition, oxytocin enhances inhibitory transmission and excites ACC interneurons. Similar results are obtained by using selective optical stimulation of oxytocin-containing projecting terminals in the ACC in animals with neuropathic pain. Our results demonstrate that oxytocin acts on central synapses and reduces chronic-pain-induced anxiety by reducing pre-LTP. [Display omitted] •Oxytocin microinjected into ACC attenuates injury-related pain and anxiety responses•Oxytocin blocks the maintenance of pre-LTP, but not post-LTP•Oxytocin depolarizes the interneurons and decreases the ratio of E/I transmission•Activation of PVN-ACC pathway blocks pre-LTP and has analgesic and anxiolytic effects Li et al. report that microinjection of oxytocin into the ACC attenuates nerve-injury-induced nociceptive and anxiety behavioral responses. They show that oxytocin blocks the maintenance of pre-LTP and potentiates inhibitory transmission. Optical activation of endogenous oxytocin release in the ACC blocks pre-LTP and produces analgesic and anxiolytic effects.